Sharīʿah Standard for Crypto Assets in Indonesia: A Localised Framework - Devin Halim; Ahmad Fathi Alkatiri (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2026)
Sharīʿah compliance of crypto assets is examined in the Indonesian context by placing fiqh assessment within the domestic regulatory framework. In this context, crypto is legally treated as a digital commodity rather than currency. Therefore, this study aims to formulate an operational screening framework to distinguish potentially Sharīʿah-compliant and non-compliant crypto assets based on underlying characteristics, asset structure, valuation basis, and transaction mechanisms. Fiqh muʿāmalah principles, the 2021 MUI Ijtimāʿ ʿUlamāʾ ruling, relevant DSN-MUI fatwās, AAOIFI references, and Indonesian crypto regulations are analysed using a qualitative doctrinal legal method. The proposed framework distinguishes between asset-level and transaction-level screening, particularly in assessing halal underlying utility, gharar, maysir/qimār, ribā exposure, silʿah requirements, and transaction validity. The framework is applied to four illustrative assets, namely Bitcoin (BTC), Ethereum (ETH), CasinoCoin (CSC), and Blockchain Capital Token (BCAP). The results show that Ethereum satisfies the utility criterion, subject to Sharīʿah-compliant use and transaction mechanisms. Bitcoin remains a contested case because legal classification as a commodity does not automatically resolve valuation gharar and silʿah concerns. CasinoCoin is non-compliant due to its direct connection with gambling, while BCAP requires further review because of insufficient clarity regarding contract structure, portfolio composition, and Sharīʿah screening. The study contributes a structured and reviewable screening model to support Sharīʿah governance, regulatory development, and technology-based Islamic financial innovation in Indonesia.